Feasibility Aspects of Exploring Exercise-Induced Neuroplasticity in Parkinson’s Disease: A Pilot Randomized Controlled Trial - Hanna Johansson; Malin Freidle; Urban Ekman; Ellika Schalling; Breiffni Leavy; Per Svenningsson; Maria Hagströmer; Erika Franzén (Parkinson's Disease)
Background. Recent studies indicate that exercise can induce neuroplastic changes in people with Parkinson’s disease (PwPD). Reports of feasibility outcomes from existing pilot trials however are, of date, insufficient to enable replication by others in larger definitive trials. Objective. To evaluate trial design for a definitive trial by exploring process and scientific feasibility. Methods. The trial design was a parallel-group RCT pilot with a 1 : 1 allocation ratio to either HiBalance or an active control group (HiCommunication). Both groups received one-hour sessions twice weekly, plus home exercises weekly, for 10 weeks. Participants with mild-to-moderate Parkinson’s disease (PD) were recruited via advertisement. Assessment included physical performance, structural and functional MRI, blood sampling, neuropsychological assessment, and speech/voice assessment. Process and scientific feasibility were monitored throughout the study. Process feasibility involved recruitment, participant acceptability of assessments and interventions, assessment procedures (focus on imaging, blood sampling, and dual-task gait analysis), and blinding procedures. Scientific feasibility involved trends in outcome response and safety during group training and home exercises. Data are presented in median, minimum, and maximum values. Changes from pre- to postintervention are reported descriptively. Results. Thirteen participants were included (4 women, mean age 69.7 years), with a recruitment rate of 31%. Attendance rates and follow-up questionnaires indicated that both groups were acceptable to participate. Image quality was acceptable; however, diplopia and/or sleepiness were observed in several participants during MRI. With regard to dual-task gait performance, there appeared to be a ceiling effect of the cognitive tasks with seven participants scoring all correct answers at pretest. Blinding of group allocation was successful for one assessor but was broken for half of participants for the other. Conclusions. The overall trial design proved feasible to perform, but further strengthening ahead of the definitive RCT is recommended, specifically with respect to MRI setup, cognitive dual-tasks during gait, and blinding procedures. This trial is registered with NCT03213873.